(untitled) (Global Journals of Research in Engineering, 2013)
Power factor correction PFC is a technique of counteracting the undesirable effects of electric loads that create a power factor that is less than one Power factor correction may be applied either by an electrical power transmission utility to improve the stability and efficiency of the transmission network or correction may be installed by individual electrical customers to reduce the costs charged to them by their electricity supplier Many control methods for the Power Factor Correction PFC have been proposed This work describes the design and development of a power factor corrector using PIC Programmable Interface Controller microcontroller chip Measuring of power factor from load is achieved by using PIC Microcontroller-based developed algorithm to determine and trigger sufficient switching of capacitors in order to compensate demand of excessive reactive power locally thus bringing power factor near to unity